Propuesta de una alternativa de cambio de agentes curtientes en la etapa de curtido para la empresa Ecocaimán (2018)
The objective of this degree work is to propose an alternative to change tanning agents in the tanning stage for the company Ecocaimán, which are free of chromium, that is to say compounds that are friendly to the environment. A bibliographic review is made on the most common tanning techniques, then the tanning agents representative of each technique are investigated; by means of the criterion of selection of weighted sums, the use of mimosa extract is established and by consultation in the tanning industry, a mixture of tanning aldehydes is chosen as a second alternative. Once the mimosa and the mixture of aldehydes with tanning power have been chosen, experimentation is carried out in the Ecocaimán production plant. The experimental design was developed with two independent variables: the type of tanning agent, one aldehyde (A) and another mixed (B), the latter is a mixture between aldehyde and vegetable tanning agents; The second independent variable is the composition of water, which has three levels: 100% water PTAR (1), 70% water aqueduct and 30% water PTAR (2) and, the last 30% water aqueduct and 70% water PTAR (3). The experimentation is carried out according to the standardized procedure for tanning skins. It starts from the first ribera stage and ends with the stage, manual operation of the retanned and greased stage. The experimentation process is carried out for 6 test alternatives with 2 replications for each one and each tanning process lasts approximately 2 and a half months.